Recognition of DNA structure by 434 repressor. - Koudelka, G B (1998)
In complexes of bacteriophage 434 binding sites with 434 repressor the central 4 bp of the 14 bp site are not contacted by the protein, although changes in these bases alter binding site affinity for the repressor. Our previous data suggested that the ability of the non-contacted central bases to be overtwisted in repressor-DNA complexes governs affinity of the binding site for 434 repressor. This idea was tested by examining the affinity of two central sequence variant 434 binding sites for 434 repressor as a function of binding site average twist. The 434 repressor preferred the relatively overwound binding site to the two more underwound forms. The greatest affinity enhancement resulting from increasing twist was observed with a binding site that is relatively underwound and more resistant to twisting deformation. Consistent with the idea that 434 repressor overtwists its binding site upon DNA binding, we show that 434 repressor is capable of binding to sites bearing a single base insertion in their center (a 15mer), but binds poorly to binding sites bearing central base deletions (12mer and 13mer). The N-terminal dimer interface plays a large role in determining 434 repressor central base preferences. Mutations in this interface eliminate central base discrimination and/or site size preferences. These mutations also lead to changes in the size of the repressor footprint on the various sized DNA sites that are consistent with their binding characteristics.